2017
DOI: 10.1007/s00418-017-1594-0
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical localization of histidine-rich glycoprotein in human skeletal muscle: preferential distribution of the protein at the sarcomeric I-band

Abstract: Histidine-rich glycoprotein (HRG) is a relatively abundant plasma protein that is synthesized by parenchymal liver cells. Using Western blot analysis and immunoperoxidase techniques, we have previously shown the presence of HRG in human skeletal muscle. This paper reports the results of immunofluorescence experiments carried out on sections of human normal skeletal muscle biopsies to investigate the subcellular localization of HRG. The HRG localization was also compared with that of skeletal muscle AMP deamina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 29 publications
2
9
0
Order By: Relevance
“…1 3 distribution of HRG in human skeletal muscle, and comparing its distribution to that of AMPD1 (Mattii et al 2017). Importantly, the immunostaining patterns observed were consistent using both self-made and commercially purchased anti-HRG antibodies.…”
Section: Restricted Distribution Of Histidine-rich Glycoprotein In Husupporting
confidence: 55%
“…1 3 distribution of HRG in human skeletal muscle, and comparing its distribution to that of AMPD1 (Mattii et al 2017). Importantly, the immunostaining patterns observed were consistent using both self-made and commercially purchased anti-HRG antibodies.…”
Section: Restricted Distribution Of Histidine-rich Glycoprotein In Husupporting
confidence: 55%
“…This new discovery, confirmed by control experiments on rat muscle fibers, is very intriguing as suggests a possible involvement of HRG in gene regulation. In fact, despite numerous data from the literature reporting the involvement of HRG in a number of important biological processes such as cell proliferation, phagocytosis of apoptotic cells, angiogenesis, and tumor progression and showing that all these activities are triggered in an indirect way, through HRG binding to cell surface molecules, 7,11,12,35 other studies have already described HRG cell internalization 21,22,36 and demonstrated a cytoplasmic HRG localization 19,23 and function 14,16 in skeletal muscle. Although the analysis of HRG amminoacidic sequence showed that HRG lacks the classical nuclear localization sequences that “tag” proteins for nuclear import, alternative nuclear localization mechanisms, which are likely to account for a large amount of nuclear traffic, could be involved in HRG nuclear localization.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of serial sections of healthy human skeletal muscles, after the AMPD histoenzymatic stain and the HPRG immunostaining, showed that the immunopositivity of HPRG in Type IIB fibers was always associated with high levels of AMPD activity, whereas Type IIA and Type I fibers always gave a weak response to the HPRG antibody, even in the specimens where Type IIA fibers showed an AMPD histoenzymatic staining similar to that of IIB, suggesting a preferential association of HPRG to the AMPD isoenzyme contained in fast-twitch glycolytic fibers [ 40 ]. A recent immunohistochemical study with human gastrocnemius and quadriceps femoris has shown a localization of HPRG at the I-band level, where it shows the same distribution of actin and where AMPD1 is present in major concentration [ 52 ].…”
Section: Distribution and Localization Of Ampd Isoformsmentioning
confidence: 99%
“…We have recently demonstrated that HPRG is preferentially localized at the I-band level, where it shows the same distribution of actin and where AMPD1 is present in major concentration [ 52 ]. Based on our preliminary data that actin fragments could be isolated following the limited tryptic proteolysis of the isolated HPRG component of rabbit AMPD1 [ 113 ], we hypothesize that HPRG could be associated with the actin filament, and that the HPRG-AMPD1 complex could interact with proteins that take part in the constitution of the thin filament.…”
Section: Intracellular Distribution Data Of Striated Muscle Ampd mentioning
confidence: 99%
See 1 more Smart Citation